A new capacitance angle sensor of concentric ring multi-layer differential. (1st July 2020) - Fu, Yuchen; Fan, Wei; Jin, Huaxue; Chen, Qian
Highlights: The probe of angle sensor uses the structure of concentric ring multi-layer. The differential structure improves the range and precision of the sensor. Achieving the miniaturization of the probe. The sensor has strong anti-interference ability. Abstract: The capacitive angle sensor has good output linearity, high precision and good dynamic response. The designed sensor probe has a differential multilayer ring structure, which greatly increases the positive area of the microplate and effectively improves the range and measurement accuracy of the sensor. In addition, CAV444 and ADS1115 are used to construct the signal processing circuit system, which reduces the interference of parasitic capacitance, suppresses common mode interference, and improves measurement accuracy and sensitivity. Large range and small range calibration experiments were carried out respectively, and the nonlinear errors of the three fitting methods of polynomial, Fourier function, and sine function were analyzed. The experimental results show that in range of 0–360°, the precision of sensor is 1°, the sensitivity is 0.0198 V/°, the minimum nonlinear error is 4.89%, the hysteresis error is less than 3.72%, and the repeatability error is less than 1.78%; in range of 0–0.688°, the precision is 0.05°, the sensitivity is 4.82 V/°, the nonlinear error is 0.42%, the hysteresis error is less than 0.20%, and the repeatability error is less than 0.16%. Results indicate that the designed capacitive angle sensor has good output linearity, high precision and good dynamic response.